Analysis on Communication Influence of Official Microblogs - Nan Chen; Dingguo Yu; Yijie Zhou; Wenjuan Li (Discrete Dynamics in Nature and Society)
As an innovative way for government affairs disclosure, official microblogs have been widely used in information release, public opinion listening, and public services, which become a model of “Internet + government affairs.” The communication influence of official accounts is mainly related to the account’s attention, activity, and the posted articles. Based on AHP, we design a multi-hierarchy-rank model to filter the factors and determine the most important factors related to the influence of official microblogs. This study explores the communication influence of official microblog from the perspectives of breadth, depth, and intensity; then, a three-dimensional integration of government microblogs influence calculation model for radiation, activity, and interaction is built and a monitoring and analysis system for the communication influence of government microblog is developed; finally, about 2,800 official accounts and more than 1.5 million articles in Zhejiang Province are monitored and analyzed. According to microblog verification, our proposed calculation model not only quantifies the communication influence of official microblogs but also analyzes their dynamics and timeliness. Therefore, it helps government departments to promote the healthy and orderly development of government microblogs.